Faktor Investasi Klasik Peserta Asuransi pada Unit Link Syariah di Yogyakarta - Zahirotul Kamiliyah (AN NUR: Jurnal Studi Islam, 2022)
This research aimed to determine the classic investment factors for insurance participants on unit link Sharia in the Yogyakarta area. This research type used mixed method research (the quantitative and qualitative research). Primary data was obtained by distributing questionnaires, while the qualitative stage of data was obtained by interview, observation, and also documentation. The research results showed that classical investment factors could influence the participants' decision to invest in sharia unit link insurance. The effect is 3.0, i.e. participants stated "agree". The important aspect of consideration for participants was the image aspect of the insurance company that they currently participated in. The item that the participants considered was the company's reputation item. The lowest value aspect was the neutral Information aspect, while the lowest value item was the inflation consideration item.